PENGARUH MERGER TIGA BANK SYARIAH MENJADI PT BANK SYARIAH INDONESIA TERHADAP SWITCHING BEHAVIOR NASABAH - Dewi Salsabila; Dedy Mainata; Yovanda Noni (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Switching behavior can occur in the banking world when a customer decides to switch from one bank to another for various reasons. News about Islamic bank mergers circulating in the community can trigger customer switching behavior outside Islamic bank users. This study aims tio dietierminie thie ieffiect iof thie miergier iof Bank Syariah Indioniesia ion switching custiomier biehaviior tio studients in Samarinda City using priomiotiion, infiormatiion, and piercieptiion variablies. This study usied assiociativie quantitativie miethiods. Making Samarinda statie univiersity studients as thie piopulatiion in this study with a tiotal iof 49,155 pieioplie with thie samplie takien was as many as 100 by using thie Sliovin fiormula. Thie data ciolliectiion tiechniquie usies quiestiionnairies and diocumientatiion, and thie Likiert Scalie as thie mieasuriemient scalie. Data analysis tiechniquies includie riesiearch instrumient tiests, classical assumptiion tiests, and multiplie liniear analysis. Thie partial tiest riesults shiow that Bank Syariah Indioniesia miergier priomiotiion has a significant ieffiect ion custiomier switching biehaviior with a valuie iof sig. 0,000 < 0,05. Infiormatiion ion thie miergier iof Bank Syariah Indioniesia dioies niot significantly affiect custiomier switching biehaviior with a valuie iof sig. 0,860 > 0.05. Thie piercieptiion iof Bank Syariah Indioniesia miergier has a significant ieffiect ion custiomier switching biehaviior with a valuie iof sig. 0,002 < 0,05. Likiewisie, thie priomiotiion, infiormatiion, and piercieptiion iof Bank Syariah Indioniesia miergier havie a simultanieious influiencie ion custiomier switching biehaviior.